ISAR Sparse Aperture Imaging Algorithm for Large Size Target - 仲, 利华; 胡, 东辉; 丁, 赤飚; 张, 问一 (Journal of radars = Lei da xue bao, 2012)
A novel algorithm for larger size target imaging in sparse aperture is presented in this paper for Inverse Synthetic Aperture Radar (ISAR). In the proposed method, azimuth compressing is done in the range frequency domain to avoid Migration Through Range Cell (MTRC), and Compress Sensing (CS) is introduced to take place of FFT to reduce the Peak Side Lobe Ratio (PSLR), meanwhile a basis matrix changing with the range frequency is constructed to eliminate the coupling between range frequency and azimuth time. Simulation results validate the feasibility of the approach.